A Comprehensive Review of Network and Communication in IoT Systems - MD ROSLAN, MOHD SALLEH; Loh, Yin Chyuan; Hamzah, Shipun Anuar (Emerging Advances in Integrated Technology, 2025)
The Internet of Things (IoT) represents a transformative domain in technology, integrating devices equipped with sensors, software, and connectivity to enable data exchange and automation. This paper discusses IoT networks and their communication protocols, highlighting applications across smart homes, industrial settings, and agriculture. It explores core technologies such as Wi-Fi, Bluetooth, Cellular (4G/5G), and LoRa, emphasizing their advantages and limitations. The layered IoT architecture, from perception to application, is reviewed, detailing its impact on system performance. Challenges related to energy consumption, security, and scalability are also addressed. Key findings underscore the importance of tailored communication solutions and integrated protocols for optimized IoT performance.